Labile imidazolium salt protected palladium nanoparticles - Lu, Jung-Tang (Langmuir : the ACS journal of surfaces and colloids, 2014)
An imidazolium (Im) salt with two long alkyl substituents at N atoms is employed to prepare cubelike palladium nanoparticles (PdNPs). The bilayer nature of the capped Im salts is characterized by thermogravimetric analysis and NMR studies. These capped Im salts are labile, as evidenced by their displacement reaction with dimethylaminopyridine, and the observation of fast exchange between those free and capped Im salts on the NMR time scale. NMR results also show that these capped Im salts exhibit different diffusion rates, and interesting spinning rate dependent chemical shifts. These cubelike PdNPs could catalyze the Suzuki coupling of aryl chlorides and boronic acids with high yields in 10 min, even at room temperature